Managing idiopathic intracranial hypertension in pregnancy: practical advice. Issue 4 (21st April 2022) - Thaller, Mark; Wakerley, Benjamin R; Abbott, Sally; Tahrani, Abd A; Mollan, Susan P; Sinclair, Alexandra J
Abstract : Idiopathic intracranial hypertension (IIH) is more common in women of reproductive age who have obesity, yet there is little information on its management specifically in pregnancy. Women with IIH should plan their pregnancy including discussing contraception before pregnancy, recognising that hormonal contraceptives are not contraindicated. Potentially teratogenic medications including acetazolamide and topiramate are not recommended during pregnancy or in those with immediate plans to conceive; prescribing acetazolamide in pregnancy must only follow discussion with the patient and their obstetrician. Ideally, patients should aim to achieve disease remission or control before pregnancy, through optimising their weight. Although weight gain is expected in pregnancy, excessive weight gain may exacerbate IIH and increase maternal and fetal complications; evidence-based recommendations for non-IIH pregnancies may help in guiding optimal gestational weight gain. The vast majority of women with IIH can have a normal vaginal delivery, with spinal or epidural anaesthesia if needed, provided the papilloedema is stable or the IIH is in remission.